Influence of Sophisticated Accounting Systems On Transaction Expansion In Islamic Financial Institutions During The Digital Era - Wahyudhi, Imam; Syarif, Siti Alwya (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2025)
The rapid advancement of technology in the modern era has fundamentally transformed various sectors, including Islamic banking. The integration of digital accounting applications has become a key element in enhancing operational efficiency and transaction growth while ensuring compliance with Sharia principles. This study explores the role of accounting applications in driving transaction growth in Islamic banking, focusing on their contributions to strengthening Sharia compliance, operational efficiency, customer satisfaction, and risk mitigation. The research employs a qualitative approach through semi-structured interviews with key stakeholders, including financial managers, IT professionals, and Sharia compliance officers. Document analysis, such as reviewing financial reports and compliance-related documents, was also conducted to support the findings. The results reveal that accounting applications offer significant benefits, including reducing human errors, improving accuracy, and enhancing transparency in financial processes. Furthermore, these applications enable innovation in Islamic financial products, support operational expansion, and ensure compliance with Islamic law in every transaction. For instance, features such as automated financial reporting and real-time monitoring are highly effective in detecting potential Sharia violations at an early stage. Thus, accounting applications not only serve as technical tools but also as strategic assets that facilitate sustainable growth and competitiveness for Islamic banking in the digital era.